Criteria For Evaluating Environmental Sustainability Performance of Building Projects: A Review - Sidik, M. A.; El Fathali , Hassan Ibrahim; Ayarkwa, Joshua; Acheampong, Alex; Osei-Tutu, Safowaa; Afful , A Essanuwaa (Transactions on Engineering and Computing Sciences, 2024)
This study aimed at identifying the criteria for evaluating environmental sustainability performance (ESP) of building projects and examining the research developments and performance (‘hot’ themes, status quo, and research gaps) in the research domain. A literature search was conducted using the Scopus search engine, augmented by Google Scholar, to identify 59 relevant articles for analysis. A bibliometric analysis was undertaken with the use of VOSViewer to better understand the broad literature on ESP of building projects. Content analysis allowed for a systematic review of the selected articles to reveal the criteria for evaluating ESP of building projects in the literature. Among the criteria identified include energy, emissions, waste, materials, water, and land/site. These were grouped into Environmental Management, Resource Consumption and Protection, Design, Policies and Certification, and Preservation, for better appreciation and holistic understanding of building project evaluation criteria. The research “hot” themes were ‘life-cycle assessment’, ‘sustainability in building projects’, ‘environmental assessment’ and ‘multi-criteria decision-making’, and the research status quo was ‘life-cycle assessment’, ‘analytical hierarchy process‘, ‘key performance indicators’, and ‘building information modeling’. Research gaps identified from the study include ‘Performance evaluation’, ‘Buildings’, ‘Key performance indicators’. Grouping ESP evaluation criteria offers a holistic understanding of building project evaluation criteria, enhancing understanding and application in the industry.